Giant magnetoresistance resulting from superzone gap in spin-frustrated rare-earth-based aluminide: DyFe2Al10 - Pal, Koustav; Dey, Suman; Das, I (Journal of physics. Condensed matter, 2024)
The magnetic properties of orthorhombic aluminides have recently been the subject of investigation, revealing several intriguing phenomena within this class of materials. However, the exploration of their magnetic and electrical transport phenomena has remained somewhat limited. In this study, we delve into the magnetic and electrical transport characteristics of one such material from that group which is DyFe2Al10(DFA). Our findings go beyond classifying this material as a simple antiferromagnet; but it posses a short range ferromagnetic ordering apart from helical spin structure of Dy3+. It exhibits a metamagnetic transition and spin glass behavior below its Néel temperature (TN). Our analysis of electrical magnetotransport behavior indicates the emergence of an antiferromagnetic superzone gap, resulting in a significant enhancement in magnetoresistance effect. This discovery paves the way for a class of materials with complex interactions and notable magnetoresistance properties.The magnetic properties of orthorhombic aluminides have recently been the subject of investigation, revealing several intriguing phenomena within this class of materials. However, the exploration of their magnetic and electrical transport phenomena has remained somewhat limited. In this study, we delve into the magnetic and electrical transport characteristics of one such material from that group which is DyFe2Al10(DFA). Our findings go beyond classifying this material as a simple antiferromagnet; but it posses a short range ferromagnetic ordering apart from helical spin structure of Dy3+. It exhibits a metamagnetic transition and spin glass behavior below its Néel temperature (TN). Our analysis of electrical magnetotransport behavior indicates the emergence of an antiferromagnetic superzone gap, resulting in a significant enhancement in magnetoresistance effect. This discovery paves the way for a class of materials with complex interactions and notable magnetoresistance properties.